Precursor-concentration-controlled Morphology of TiO2 Nanorod/Nanoflower Films for Enhanced Photoelectrochemical Water Splitting and Investigating Their Growth Mechanism - Anaam, Sawsan Abdullah Abduljabbar; Sahdan, Mohd Zainizan (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Titanium dioxide (TiO2) has been considered as one of the most promising photocatalysts for photoelectrochemical (PEC) water splitting. Therefore, numerous efforts have been devoted to improving its PEC water splitting performance. In this study, TiO2 nanorod/nanoflower (NRF) films with controlled morphology were synthesized on fluorine-doped tin oxide (FTO) glass substrates by following a facile one-step hydrothermal method. The TiO2 NRF films were characterized by X-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), energy-dispersive X-ray spectrometer (EDS), and ultraviolet-visible (UV-Vis) spectrophotometer. FE-SEM showed that the TiO2 films are composed of a simultaneous growth of a primary layer of TiO2 nanorod arrays (NRAs) and a second layer of TiO2 nanoflowers (NFs). The proposed growth mechanism highlighted the influence of precursor concentration on nucleation sites, affecting the preferred crystallographic plane growth of rutile TiO2 and nanorod alignment on the FTO substrate. Intriguingly, TiO2 NRF films prepared with 1.0 mL of titanium butoxide exhibited a maximum photocurrent density of 3.58 mA.cm−2 at 1.23 V versus (vs.) the reversible hydrogen electrode (RHE), along with a maximum photoconversion efficiency of 0.69%. The enhanced photocurrent density and photoconversion efficiency were attributed to the optimum thickness in the range of 4.52-7.31 µm, which caused the film to be formed with a unique morphology of the primary layer with well-vertically aligned nanorods and the second layer of flowers consisting of numerous rods stacked on top of one another. This study demonstrates the importance of designing semiconductors with 1D nanorod/3D nanoflower structures as high-performance photoelectrodes for PEC water splitting. Copyright © 2024 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).